Hydrophobic Graphene Quantum Dots for Defect Passivation and Enhanced Moisture Stability of CH3NH3PbI3 Perovskite Solar Cells. Issue 7 (11th July 2022) - Khorshidi, Elahe; Rezaei, Behzad; Blätte, Dominic; Buyruk, Ali; Reus, Manuel A.; Hanisch, Jonas; Böller, Bernhard; Müller-Buschbaum, Peter; Ameri, Tayebeh
Abstract : Perovskite Solar Cells In article number 2200023, Behzad Rezaei, Tayebeh Ameri, and co‐workers applied the hydrophobic bifunctional graphene quantum dots, containing amide and alkyl chains, as an efficient interface modifier in perovskite solar cells to enhance the quality of perovskite films, passivate the defects at the surface and grain boundaries, and facilitate the hole extraction. As a result, perovskite solar cells exhibit an improved efficiency of 18.30% and keep over 80% of their initial efficiency after 960 h under ambient air.